A Comparative Study of ICT Innovation Policy for the Countries Development Perspective - Saleem, Ayesha; Higuchi, Kiyohide (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2012)
In the globalized environment, the economic growth significantly depends on the countries capacity to develop, to apply new technologies and vice versa. Diffusion of information communication technologies is a global phenomenon. Despite of rapid globalization there are considerable differences between nations in terms of adoption and usage of new technologies. This paper aims to draw together the highly eclectic literature on the diffusion of Information and Communication Technology (ICT) Innovation in order to know what have been done, highlight the generic issues, relevant to policy and will initiate further research and develop potential opportunities. This paper also highlight the low level and high level income countries data and ICT policies frame work to draw conclusions and some case studies as an example. The objective is to review the finding the social economic factor for diffusion of ICT Innovation to make policy recommendation for the development of the country.